Knowledge, Attitudes and Practices of Communal Goat Farmers on the Prevalence and Control of Gastrointestinal Nematodes in Northern KwaZulu-Natal, South Africa - Khanyisani Cyril Ndwandwe; Michael Chimonyo; Ana Mbokeleng Tsotetsi-Khambule; Munyaradzi Christopher Marufu (Journal of Parasitology Research)
Gastrointestinal nematodes (GINs) are a significant impediment to communal goat production, causing considerable economic losses, making their control imperative. The objective of this study was to determine farmers’ knowledge, attitudes and practices on the control of GIN in communal goat flocks. A structured close-ended questionnaire was used to conduct face-to-face interviews with communal goat farmers (n=384) across four local municipalities in uMkhanyakude District Municipality. Elderly farmers were 1.4 times more likely to underdose compared to younger farmers (p<0.05). Diarrhoea and emaciation were the most reported clinical signs observed in goat flocks. Farmers were aware of clinical signs of GIN infections (p<0.01) on their farms. However, lack of professional veterinary assistance (p<0.01), low socioeconomic status and low levels of education (p<0.01) reduce the effectiveness of GIN control. Farmer’s inability to read manufacturer’s instructions was associated with incorrect dosing (p<0.05), which contributed to ineffective management and worsened the impacts of GIN infections. An immediate intervention is required from various stakeholders to achieve sustainable nematode control, with a particular emphasis on women, the elderly farmers and those with low levels of education.